Fostering participation in digital public health interventions: The case of digital contact tracing - Dominik Rehse; Felix Tremöhlen (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
The SARS-CoV-2 pandemic has made all the more clear that public health is a public good. Public health interventions try to encourage contributions to this public good. Digital public health interventions are increasingly being used to complement traditional public health interventions. The rollout of digital contact tracing apps during the SARS-CoV-2 pandemic is a prominent example. We review the literature on how participation in such digital public health interventions could be fostered, provide an overview of digital contact tracing as one such intervention, provide policy recommendations on how to increase its adoption and usage as well as recommendations for further research.
Keywords: H41; I12; I18; 330; Public health; Public good; Public health intervention; Digital contact tracing